Nursing Care for Oxygenation Needs Disorder in Patients Diagnosed with Bronchitis in the Jimbaran Lama Ward - Komariyah, Oom; Dwi Hikmatun, Khaerunnisa; Sari, Diana; Fitriyani, Risma; Purbasari, Dwiyanti (Al Makki Health Informatics Journal, 2024)
Ineffective airway clearance is one of the oxygenation disorders in patients with respiratory disorders (bronchitis). One of the practical nursing actions is to cough effectively to remove mucus in the respiratory tract. This study aimed to determine and analyze nursing care for impaired oxygenation needs in patients with a medical diagnosis of bronchitis in the old Jimbaran room. This research method uses a descriptive design as a nursing practice case study approach. The case study examines the respiratory rate (RR) of patients with respiratory disorders (bronchitis) after giving effective coughing measures for 3x24 hours. The results showed that the patient's RR before implementation was 24 x/min. In comparison, after being given an effective cough implementation for 3x24 hours, the RR was 20 x/min. In conclusion, nursing actions that need to be taken in patients with respiratory disorders (bronchitis) include assessing sputum production, effective coughing techniques, counseling regarding positioning, and collaborative oxygen or nebulizer administration. The implication of this study is the importance of effective coughing measures in managing bronchitis patients, including evaluation of sputum production, training in proper coughing techniques, education on proper positioning, and collaboration with oxygen or nebulizer administration as needed. Synchronization between research objectives and research conclusions. Present the research subject, research criteria, data collection methods, and data analysis.